Pemberdayaan Ibu Hamil Dalam Pencegahan Dan Deteksi Dini Terjadinya Anemia Pada Ibu Hamil Di Desa Bangun Rejo Tanjung Morawa Tahun 2025 - Ester Simanullang; Sri Muliana Putri Bakara; Nur Azizah; Dyanti SR Butar-butar; Cristoboy Vasius Bakara; Priska Estika Sianipar; Eva Ulina Lompohta Pinem (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Anemia in pregnant women can increase the risk of bleeding during labor. Therefore, early detection is crucial for preventing potential complications and preventing anemia during pregnancy. One way to empower pregnant women in this effort is through community service activities. This community service activity is a collaboration between STIKes Mitra Husada Medan and a practice in Bangun Rejo Village, Tanjung Morawa. Anemia can affect pregnant women at various stages of pregnancy. Therefore, this community service program is implemented in the form of a pregnancy class aimed at preventing and early detection of anemia. The target group includes pregnant women in their first, second, and third trimesters, with the hope of increasing their knowledge about anemia, thus creating physically and emotionally healthy mothers-to-be. The results of the community service program indicate positive changes following the community service, including an increased understanding of the symptoms of anemia, preventive measures, and active participation in early detection of anemia during pregnancy.